Forming Comfortable Microclimate in the Bus Compartment via Determining the Heat Loss - Oleksandr Kravchenko; Ivan Hrabar; Juraj Gerlici; Serhii Chuiko; Kateryna Kravchenko (Communications - Scientific letters of the University of Zilina, 2021)
Methodology of the heat outcome from the bus compartment in terms of duration factor of cooling and heating capacity is introduced. Value of the air temperature change in the compartment was calculated. The balance method of the spent heat is used to assess the level of keeping a proper temperature environment in the bus saloon when a comfortable microclimate is created for passengers via the proper conditioning system functioning. Models of the heat transmission notions were used for calculation regarding different categories of the heat load creation. A developed numeric algorithm was introduced in the article as well as a program for modelling the transitory heat processes in the compartment of the city bus equipped with an air-conditioner enabling to take into account various constructive decisions in the system of comfortable provision of city buses and model unstable heat processes.